New insights into the genome of Rhodococcus ruber strain Chol-4 - Guevara, Govinda (BMC Genomics, 2019)
BACKGROUND: Rhodococcus ruber strain Chol-4, a strain isolated from a sewage sludge sample, is able to grow in minimal medium supplemented with several compounds, showing a broad catabolic capacity. We have previously determined its genome sequence but a more comprehensive study of their metabolic capacities was necessary to fully unravel its potential for biotechnological applications. RESULTS: In this work, the genome of R. ruber strain Chol-4 has been re-sequenced, revised, annotated and compared to other bacterial genomes in order to investigate the metabolic capabilities of this microorganism. The analysis of the data suggests that R. ruber Chol-4 contains several putative metabolic clusters of biotechnological interest, particularly those involved on steroid and aromatic compounds catabolism. To demonstrate some of its putative metabolic abilities, R. ruber has been cultured in minimal media containing compounds belonging to several of the predicted metabolic pathways. Moreover, mutants were built to test the naphtalen and protocatechuate predicted catabolic gene clusters. CONCLUSIONS: The genomic analysis and experimental data presented in this work confirm the metabolic potential of R. ruber strain Chol-4. This strain is an interesting model bacterium due to its biodegradation capabilities. The results obtained in this work will facilitate the application of this strain as a biotechnological tool. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1186/s12864-019-5677-2) contains supplementary material, which is available to authorized users.